Aykut, S., Foyer, J. y Morena, E. (eds.) (2017) Globalising the climate: COP21 and the climatization of global debates. Nueva York: Earthscan y Routledge - Ramírez Cover, Alonso (2020)
¿What are the real possibilites that climate change negotiations offer a real solutions to this problem? ¿What projections of success can we imagine based on the new instruments for dealing with climate change suggested in the Conferences of Parties in Copenhagen 2009 and Paris 2015? ¿Are these instruments real inovations of global environmental governance or new and ineffective "buzzwords" in sustainable development cooperation? Simply put, ¿how do we know that global discussion on climate change is not empty political discourse destined to propose tangible actions with respect an uncertain future? The different contributions of the book Globalising the climate: COP21 and the climatization of global debates offer interesting and innovative answers to these enormous existencial questions of today.